Mercury Phytoremediation with Lolium perenne-Mycorrhizae in Contaminated Soils - Ana M. Leudo (Sustainability, 2020)
The symbiotic association between the roots of a plant and the mycelium of some fungi is identified as mycorrhizae. Symbiosis helps the plant to obtain nutrients from the soil more efficiently, and may favor the phytoremediation capacity of plants such as Lolium perenne, in soils contaminated with mercury. In this study, the morphological and molecular response was evaluated, as well as the variation in mercury accumulation in the different structures of L. perenne when associated with arbuscular mycorrhizal fungi. Association tests were performed to determine the optimal concentration of the biological inoculant and it was found that the best results were given with the proportion of one part of inoculant in three parts of soil (w/w ratio). The differential expression of the glutathione-S-transferase GST gene was evaluated through real-time PCR and the concentration of heavy metals inside and outside the plant was evaluated with inductively coupled plasma atomic emission spectroscopy (ICP). It was found that the plants that were inoculated with mycorrhizae developed longer stems and shorter roots; in the same way, the GST gene had greater expression in the stem than in the root, largely because the roots help the filtration of nutrients to the stem, retaining metals and detoxifying by GST-catalyzed glutathione.